Seed Germination and Physiological Response of Sunflower (Helianthus annuus L.) Cultivars under Saline Conditions - Carmen BEINSAN (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2018)
The purpose of the experiment was to highlight the germination of sunflower seeds affected by the presence of saline stress and the identification of tolerant genotypes. The biological material was represented by sunflower cvs. (Helianthus annuus L.): Coril, Select, Santiago and Fundulea-206. To simulate the saline conditions, germination solutions of sodium chloride (NaCl) were used with concentrations corresponding to the osmotic pressures -6 and -10 atm and the control seed hydration was performed with distilled water. Determination of seed germination, growth of seedling, percentage of plumules dry matter, chlorophyll content and free proline were performed. The experimental data obtained suppose the existence in the assimilation apparatus of sunflowers seedling subjected to stress a competitive chlorophyll/free proline biosynthesis processes. The experimental results regarding the effect of salinity on seed germination and seedling growth revealed important differences between genotypes. The radicle growth in the germination process were strongly affected by saline excess, with significant differences between cultivars. Saline stress results in significant reductions in the amount of chlorophyll, and high levels of free proline. It can be observed that with the increase of the stress level the percentage of the dry matter increases, indicating an accentuated water deficit.